Analisis Deskriptif Komparatif Pemanfaatan ChatGPT, Kualitas Pemahaman, dan Efisiensi Tugas Berdasarkan Status Kerja Mahasiswa - Jonathan Wijaya; R Widya Henisaputri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The use of ChatGPT in academic activities may be perceived differently in relation to students’ understanding and task efficiency. Differences in academic demands between working and non-working students may also lead to different patterns of use. This study aimed to describe ChatGPT Utilization, Quality of Understanding, and Task Efficiency, compare the three constructs according to student employment status, and compare Quality of Understanding and Task Efficiency within the same respondents. A quantitative descriptive-comparative design was employed. Data were collected from 101 Universitas Universal students selected through purposive sampling using a four-point Likert-scale questionnaire. Instrument evaluation resulted in 26 final items across three constructs, with Cronbach’s Alpha values ranging from 0.787 to 0.913. The Mann–Whitney U test indicated no significant differences between working and non-working students in ChatGPT Utilization (p=0.923), Quality of Understanding (p=0.244), or Task Efficiency (p=0.079). The Wilcoxon Signed-Rank Test showed that the mean item score for Task Efficiency was higher than that for Quality of Understanding, at 3.260 and 3.000, respectively (Z=−5.779; p<0.001; r=0.593). Based on respondents’ perceptions, ChatGPT use was more prominent in supporting practical and efficient task completion than in the quality of understanding, while student employment status did not produce meaningful differences across the three constructs. This study contributes empirical evidence by distinguishing utilization, understanding, and efficiency as separate aspects and provides a practical basis for higher education institutions to guide ChatGPT use while maintaining information verification and students’ understanding processes.